Airports’ crisis management processes and stakeholders involved - Mantzana, Vasiliki (Array, 2020)
Airports are exposed to various physical incidents that can be classified as aviation and non-aviation related incidents, including terrorist attacks, bombings, natural disasters (e.g. earthquake or tsunami and man-made disasters such as terrorist attacks) etc. (Kanyi, Kamau, & Mireri, 2016). In addition to this, cyber-attacks to airport operations are emerging especially with the increasing use of Information Systems (IS), such as electronic tags for baggage handling and tracking, remote check-in, smart boarding gates, faster and more reliable security screening technologies and biometric immigration controls etc. Any physical or cyber incident that causes loss of infrastructure or massive patient surge, such as natural disasters, terrorist acts, or chemical, biological, radiological, nuclear, or explosive hazards could affect the airports’ services provision and could cause overwhelming pressure. During the crisis management, several stakeholders that have different needs and requirements, get involved in the process, trying to cooperate, respond and support recovery and impact mitigation. The aim of this paper is to present a holistic security agenda that defines the stakeholders involved in the respective processes followed during the crisis management cycle. This agenda is based both on normative literature, such as relevant standards, guidelines, and practices and on knowledge and feedback extrapolated from a case study conducted in the context of the SATIE project (H2020-GA832969). In meeting paper’s aim, initially the normative review of the phases of the crisis management cycle (preparedness, response, recovery and mitigation) in the context of airports as well as general practices applied, are presented. Moreover, the key airport stakeholders and operation centres involved in airports operations, as well as during the crisis management are analysed.